Efferocytosis as One of the Mechanisms for Realizing the Therapeutic Effects of Mesenchymal Stem Cells - Blinova, G.A.; Yarygin, K.N.; Kholodenko, I.V. (Biomedical Chemistry: Research and Methods, 2024)
Mesenchymal stem cells (MSCs) stimulate regeneration and exhibit unique immunomodulatory properties, which makes them attractive for use in cell therapies of a wide range of pathologies. The clinical use of MSCs is hampered by the insufficiently clear understanding of their therapeutic action mechanisms. It has been reliably proven that MSCs after transplantation quickly die in the recipient's body by the mechanism of apoptosis and are cleared by professional, such as macrophages, and non-professional phagocytes, including endothelial cells, hepatocytes, resident stem cells of various tissues, including MSCs. The ingestion and processing of apoptotic cells by the phagocytes was named efferocytosis. Despite rapid elimination of transplanted cells, in most cases MSC transplantation leads to positive therapeutic effects. Clearance of apoptotic MSCs affects phagocytes, changing their phenotype, secretome, and further behavior. This review presents the basic molecular mechanisms of efferocytosis, examines the clearance of apoptotic MSCs and their therapeutic effects in various pathologies in the context of their efferocytosis by various types of phagocytes.